Cutaneous myiasis complicating squamous cell carcinoma: a case report with literature review (Dermatology Reports, 2025)
Myiasis is derived from the Greek word “myia”, which means “fly”. Zumpt, a German entomologist, defined this condition as the infestation of living humans and vertebrate animals by dipterous larvae that feed on living and dead host tissue, liquid body substances, or ingested food for a certain period. Myiasis is a rare complication that can occur in advanced squamous cell carcinoma (SCC). This report describes a rare cutaneous SCC of the face complicated by myiasis. A 70-year-old male patient presented with cutaneous SCC that involved the left lateral side of the nose, medial canthus, and left lower eyelid. The patient complained of multiple live maggots crawling out from a large wound. The larvae were isolated, examined microscopically, and identified as Dermatobia spp. The patient was treated with ivermectin, albendazole, and clindamycin, which were associated with the mechanical removal of the larvae. In the past decade, several case reports have described instances of cutaneous myiasis in head and neck malignancies. These cases were primarily linked to squamous cell carcinoma and involved patients over the age of 60. Additionally, the majority of the reported cases were from India. Myiasis can complicate SCC, particularly in patients who refuse treatment. Combining ivermectin, albendazole, and clindamycin may be a practical approach to managing myiasis.